Bridging present and future of brain-computer interfaces: an assessment of impacts - Velloso, Gabriel Teykal (2012)
Based on the report for the “Project III” unit of the PhD programme on Technology Assessment under the supervision of Prof. António B. Moniz. This report was discussed also at the 2nd Winter School on Technology Assessment held at Universidade Nova de Lisboa, Caparica Campus, Portugal on December 2011.